2002
DOI: 10.1063/1.1458684
|View full text |Cite
|
Sign up to set email alerts
|

Radial structure of a low-frequency atmospheric-pressure glow discharge in helium

Abstract: The spatial structure of a low-frequency atmospheric-pressure glow discharge was studied experimentally. The radial current distribution and discharge light emission were simultaneously measured at different phases during the ac voltage cycle. The glow discharge is formed by a radially propagating ionization wave. We also observed discharge regimes with several current pulses per half cycle corresponding to the successive, spatially separated breakdowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
106
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 10 publications
16
106
3
2
Order By: Relevance
“…The manifestation of multiple breakdowns per half cycle is also addressed, because it is in close relation with the power consumption. Such additional breakdown pulses can be due to spatially separated breakdowns, as was demonstrated by Mangolini et al, 1 or can be due to temporally separated breakdowns, as was demonstrated by Shin et al 2 The investigation in the present letter concerns only the temporally separated breakdowns. Based on these studies we can obtain a clear understanding of the governing mechanisms in the discharge.…”
mentioning
confidence: 74%
“…The manifestation of multiple breakdowns per half cycle is also addressed, because it is in close relation with the power consumption. Such additional breakdown pulses can be due to spatially separated breakdowns, as was demonstrated by Mangolini et al, 1 or can be due to temporally separated breakdowns, as was demonstrated by Shin et al 2 The investigation in the present letter concerns only the temporally separated breakdowns. Based on these studies we can obtain a clear understanding of the governing mechanisms in the discharge.…”
mentioning
confidence: 74%
“…Two discharge regimes are discussed for these DBDs, operation in glow and Townsend mode [13]. At elevated pressure and operation in noble gases these devices can be observed to operate in a so called 'glow' or 'pseudo-glow' regime and are in that case characterised as atmospheric pressure glow discharges (APGD) [10,11,12]. Differing from the microplasma array these DBD's are typically set up in plane-parallel geometry with electrode gaps of mm dimension and diameters of several centimetres.…”
Section: Discharge Modementioning
confidence: 99%
“…A thicker dielectric reduces the observed current peak and shifts the operating point along the subnormal branch of the current voltage characteristic from a glow-like towards a more Townsend-like appearance. Detailed 2D models [30] could also reproduce observed radially moving current fronts during the ignition phase [50] and transitions from an initially filamentary to a diffuse discharge. This can be achieved by increasing the operating frequency or the applied voltage or by decreasing the permittivity of the dielectric.…”
Section: Numerical Modelling Of Diffuse Vbdsmentioning
confidence: 99%